2020
DOI: 10.1186/s12890-020-1060-y
|View full text |Cite|
|
Sign up to set email alerts
|

Surfactant protein A as a biomarker of outcomes of anti-fibrotic drug therapy in patients with idiopathic pulmonary fibrosis

Abstract: Background Idiopathic pulmonary fibrosis (IPF) is a progressive and fibrosing lung disease with poor prognosis. Pirfenidone and nintedanib are anti-fibrotic drugs used for patients with IPF. These drugs reduce the rate of decline in forced vital capacity (FVC). Serum surfactant protein (SP)-A, SP-D, and Krebs von den Lungen-6 (KL-6) are monitoring and prognostic biomarkers in patients with IPF; however, their relationship with the therapeutic outcomes of anti-fibrotic drugs has not been investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 34 publications
4
31
1
2
Order By: Relevance
“…Thus, SP-D may be useful for observing changes in pathobiology caused by treatment with pirfenidone. Changes in circulating biomarker concentrations might predict the progression of fibrosis earlier than the apparent decline displayed by physiological parameters such as VC and diffusion capacity of the lung for carbon monoxide (DLCO), and thus might be of use in determining response to therapy in clinical practice [35][36][37]. However, the decrease in the concentrations of SP-D at week 16 in patients receiving pirfenidone was not associated with outcomes in our present study.…”
Section: Discussioncontrasting
confidence: 59%
“…Thus, SP-D may be useful for observing changes in pathobiology caused by treatment with pirfenidone. Changes in circulating biomarker concentrations might predict the progression of fibrosis earlier than the apparent decline displayed by physiological parameters such as VC and diffusion capacity of the lung for carbon monoxide (DLCO), and thus might be of use in determining response to therapy in clinical practice [35][36][37]. However, the decrease in the concentrations of SP-D at week 16 in patients receiving pirfenidone was not associated with outcomes in our present study.…”
Section: Discussioncontrasting
confidence: 59%
“…This is consistent with earlier findings on other EBC cytokines [20]. There are, however, reports on antifibrotic treatment-induced changes in the cytokine profile in serum [37,38], but these did not include the cytokines investigated in the present study. Ronan et al showed an increase in the level of IL-10 and IL-4 as well as VEGF-A but not IL-6, IL-8, IL-15 and TNF-α over a six-month treatment period with pirfenidone [18].…”
Section: Discussionsupporting
confidence: 93%
“…We did not observe any significant changes in lung function over the treatment period what may be interpreted as a sign of disease stability. In the study by Yoshikawa et al, an FVC decline of ≥10% and/or a TLCO decline of ≥15% of baseline was observed in 34.7% of the investigated group after six to nine months of observation [38]. Majewski et al reported a more favorable treatment response, with FVC and TLCO stability in 60.8% and 87.1% of the patients over six months of treatment with pirfenidone, respectively [39].…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, our study indicated the changes in serum levels of SP-A and KL-6 correlated signi cantly with changes in respiratory function, which re ects disease activity. These results are also consistent with other reports [6,10,11,26,28,32,33,[35][36][37][38]. Because of the di culty of respiratory function tests for patients of ILD, this evidence strongly supports the value of biomarkers in monitoring the activity of ILDs.…”
Section: Discussionsupporting
confidence: 92%
“…In patients with IPF, SP-A is a useful predictor of mortality and disease progression [15]. It was suggested that serum SP-A has a potential as a biomarker of the therapeutic outcomes of anti-brotic drugs [26]. However, although there are increasing reports about KL-6 and SP-A in the ILD context, there has been little investigation of the difference between SP-A and KL-6 as biomarkers.…”
Section: Discussionmentioning
confidence: 99%